Awareness about Artificial Neural Network (ANN) use in health system among physicians in Benghazi (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Artificial neural networks are computational paradigms based on mathematical models that unlike traditional computing have a structure and operation that resembles that of the mammal brain. One of the original aims of artificial neural networks (ANN) was to understand and shape the functional characteristics and computational properties of the brain when it performs cognitive processes such as sensorial perception, concept categorization, concept association and learning. However, today one of the most uses of ANN in the health system are Diagnosis, predication and classification by using different and recent techniques.This is a paper pilot orientation use of ANN in the health system among physicians in Benghazi as a tool in their diagnostic field. Our target population was physicians in the Benghazi medical center and polyclinics with different professions, where the participates 200 with different age groups by filling one of two types of survey (online- in person). Based on the results of surveyBased on the results of survey we found 89% of physicians didn’t have any information about ANN, 95% didn’t read any paper about ANN technology, 98% didn’t use ANN as tool in diagnostic field, in addition, 60% they think it has value in using as tool in diagnostic field.